2023
DOI: 10.1038/s41467-023-37267-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial assembly of inner ear hair cell ankle link condensate through phase separation

Abstract: Stereocilia are actin-based cell protrusions of inner ear hair cells and are indispensable for mechanotransduction. Ankle links connect the ankle region of developing stereocilia, playing an essential role in stereocilia development. WHRN, PDZD7, ADGRV1 and USH2A have been identified to form the so-called ankle link complex (ALC); however, the detailed mechanism underlying the temporal emergence and degeneration of ankle links remains elusive. Here we show that WHRN and PDZD7 orchestrate ADGRV1 and USH2A to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…In addition, we showed the localization of ADGRV1 in mitochondria-associated ER membranes (MAMs), important for the maintenance of Ca 2+ -homeostasis (Krzysko et al, 2022(Krzysko et al, ), 2022 and that ADGRV1 controls autophagy processes and cellular proteostasis (Linnert et al, 2023). Moreover, others and we have previously shown that the USH2C protein ADGRV1 is part of the USH interactome interacting with both other USH2 proteins, usherin (USH2A) and whirlin (USH2D), and the two USH1 proteins myosin VIIa (USH1B) and harmonin (USH1C) (Reiners et al, 2005;van Wijk et al, 2006;Michalski et al, 2007;Wang et al, 2023). The putative USH1J protein CIB2 also interacts with the USH proteins whirlin and myosin VIIa (Riazuddin et al, 2012), and the interaction between ADGRV1 and CIB2 that we describe here confirms that CIB2 is part of the USH interactome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed the localization of ADGRV1 in mitochondria-associated ER membranes (MAMs), important for the maintenance of Ca 2+ -homeostasis (Krzysko et al, 2022(Krzysko et al, ), 2022 and that ADGRV1 controls autophagy processes and cellular proteostasis (Linnert et al, 2023). Moreover, others and we have previously shown that the USH2C protein ADGRV1 is part of the USH interactome interacting with both other USH2 proteins, usherin (USH2A) and whirlin (USH2D), and the two USH1 proteins myosin VIIa (USH1B) and harmonin (USH1C) (Reiners et al, 2005;van Wijk et al, 2006;Michalski et al, 2007;Wang et al, 2023). The putative USH1J protein CIB2 also interacts with the USH proteins whirlin and myosin VIIa (Riazuddin et al, 2012), and the interaction between ADGRV1 and CIB2 that we describe here confirms that CIB2 is part of the USH interactome.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant phase separation (PS) or aggregation processes have been implicated in the pathogenesis of various diseases, including neurodegenerative disorders, autism 4 , and hearing loss [7][8][9] . In this study, we employed PSMutPred to predict the PS impact ('Impact' prediction and 'Strengthen/Weaken' prediction) of missense variants from genes associated with PS-related diseases.…”
Section: Experimental Validation On the Novel Ps-related Mutations Id...mentioning
confidence: 99%
“…An increasing number of proteins are recognized for their roles via the formation of phase separation condensates. These condensates include the nucleolus and transcription factories in the nucleus 4 , stress granules 5 , and protein densities at neuronal synapses 6 and inner-ear hair cells [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%